Improvement of mechanical properties and thermal stability of biodegradable rice starch–based films blended with carboxymethyl chitosan - Rungsiri Suriyatem (2018)
© 2018 Elsevier B.V. Biodegradable blend films from rice starch (RS) and carboxymethyl chitosan (CMCh) were produced and characterized. Color, opacity, mechanical properties, thermal properties, swellability, oxygen and water permeability, and biodegradability of the RS–CMCh blend films are reported. Interaction and compatibility of films components were evaluated by using Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction. Increased yellowness, total color difference and transparency, and decreased redness, lightness and whiteness index were observed in the blend films as incorporation of CMCh increased. Addition of 50% w/w of CMCh into the RS matrix increased the tensile strength of the RS–CMCh blend film by 35% and the elongation at break by 28%. Addition of CMCh improved the thermal stability of the RS–CMCh films. Incorporation of 12, 33 and 50% w/w CMCh in the blend films increased the swelling ratio by around 850%, 3985% and 3404% at 24 h, respectively, when compared with the RS film. The oxygen permeability of all the films increased as relative humidity increased. The FTIR spectra suggested that interactions may be present between the –OH groups of RS and the COO– groups of CMCh. Scanning electron microscopy images revealed that the cross-sectional fracture surfaces of all the films were smooth and homogenous. The RS film exhibited a priming effect in the biodegradation study. The addition of 50% w/w CMCh led to a decrease in mineralization of the blend films.